Intraocular pressure predicts premature coronary atherosclerosis - Kaplan,Mehmet (2020)
SUMMARY OBJECTIVE: The aim of this study was to investigate the association between intraocular pressure (IOP) and premature atherosclerotic coronary artery disease (PACAD) by comparing central corneal thicknesses (CCTs) measurements. METHODS: One hundred-eighty-six subjects were enrolled in this cross-sectional study, 100 in the PACAD group and 86 in the control group. All participants underwent a physical examination and routine biochemical tests. Ophthalmological examinations, including IOP and CCTs measurements, were performed for each subject. Additionally, pulse wave velocity measurements were obtained and recorded. RESULTS: Participants with PACAD showed significantly higher IOP values than those without atherosclerosis (p = 0.001), and there was no statistically significant difference between the groups in terms of CCT (p = 0.343). Also, pulse wave velocity (PWV) values were statistically significantly higher in the PACAD group (p = 0.001). High IOP was not significantly associated with metabolic syndrome parameters (p > 0.05). CONCLUSIONS: A relationship was found between PACAD and IOP, but CCTs were not associated with PACAD. The IOP measurement is affected by CCT; therefore, CCT is used to correct IOP values. To our knowledge, this is the first study to report a positive relationship between PACAD and IOP based on CCTs measurements.